2016
DOI: 10.33012/2016.13463
|View full text |Cite
|
Sign up to set email alerts
|

GNSS Vertical Dilution of Precision Reduction using Terrestrial Signals of Opportunity

Abstract: and an M.S.E. in Aerospace Engineering and a Ph.D. in Electrical and Computer Engineering from The University of Texas at Austin. From 2004 through 2010 he was a research and development engineer with the LabVIEW Control Design and Dynamical Systems Simulation Group at National Instruments Corp. His research interests include estimation, navigation, autonomous vehicles, and intelligent transportation systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…As seen from (17, line 2), the VDOP value will be equal to VDOP'. This situation can be achieved with the addition of terrestrial transmitters such as pseudolites or signals of opportunity located below the user's horizon, see for example Morales et al (2016), Montillet et al (2014) and Meng et al (2004). In this continuation, let us imagine a transparent earth to the GPS signals.…”
Section: Horizontally Symmetrical (Hs) Satellite Sky Distributionmentioning
confidence: 99%
“…As seen from (17, line 2), the VDOP value will be equal to VDOP'. This situation can be achieved with the addition of terrestrial transmitters such as pseudolites or signals of opportunity located below the user's horizon, see for example Morales et al (2016), Montillet et al (2014) and Meng et al (2004). In this continuation, let us imagine a transparent earth to the GPS signals.…”
Section: Horizontally Symmetrical (Hs) Satellite Sky Distributionmentioning
confidence: 99%
“…Cellular signals can be exploited for localization either to produce a navigation solution in a standalone fashion or to aid the INS in the absence of GNSS signals . Moreover, it has been demonstrated that fusing cellular signals with GNSS signals, when available, significantly improves the positioning accuracy …”
Section: Introductionmentioning
confidence: 99%
“…SOPs are abundant, powerful, and available at various frequencies and geometric configurations, making them an attractive stand-alone navigation system whenever GNSS signals become inaccessible or untrustworthy. Even when GNSS signals are available, SOP observables can be coupled with GNSS observables to significantly improve the accuracy of the navigation solution [20].…”
Section: Introductionmentioning
confidence: 99%